Lessons from the Past: Medieval Universities and Today - Rubin, Miri (International Higher Education, 2012)
The European medieval universities are the basic model for modern universities everywhere. The medieval universities have some interesting relevance to today's debates about higher educationincluding issues such as entrepreneurialism, financing, curriculum, and others.